2018
DOI: 10.1111/nan.12525
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive amyotrophic lateral sclerosis is associated with microglial reactivity and small heat shock protein expression in reactive astrocytes

Abstract: Aims Amyotrophic lateral sclerosis (ALS) is a chronic neurodegenerative disease characterized by progressive loss of motor neurons, muscle weakness, spasticity, paralysis and death usually within 2–5 years of onset. Neuroinflammation is a hallmark of ALS pathology characterized by activation of glial cells, which respond by upregulating small heat shock proteins (HSPBs), but the exact underlying pathological mechanisms are still largely unknown. Here, we investigated the association between ALS disease duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Microglial activation is consistently detected in the motor cortex however one study also detected an increase in the dorsolateral prefrontal cortex and thalamus (Turner et al, 2004). Interestingly, microgliosis appears to associate with disease severity (Turner et al, 2004; Brettschneider et al, 2012; Zürcher et al, 2015), with a recent study suggesting microgliosis is specifically associated with rapid disease progression (Gorter et al, 2018). Taking a data-driven approach, another recent work uncovered networks of genes that associate with motor neuron pathology in human ALS brain.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
See 1 more Smart Citation
“…Microglial activation is consistently detected in the motor cortex however one study also detected an increase in the dorsolateral prefrontal cortex and thalamus (Turner et al, 2004). Interestingly, microgliosis appears to associate with disease severity (Turner et al, 2004; Brettschneider et al, 2012; Zürcher et al, 2015), with a recent study suggesting microgliosis is specifically associated with rapid disease progression (Gorter et al, 2018). Taking a data-driven approach, another recent work uncovered networks of genes that associate with motor neuron pathology in human ALS brain.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Small heat shock proteins (HSPBs) are important chaperones that reduce protein misfolding and aid in misfolded protein degradation. A recent study has found that in human ALS spinal cord, rapidly progressing disease was associated with increased HSPB5 and HSPB8 in astrocytes (Gorter et al, 2018). Furthermore, a recent rat model with restricted mutant human TDP-43 (M337V) expression in astrocytes, displayed a progressive paralysis due to loss of motor neurons in the spinal cord (Tong et al, 2013).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…It has been shown that, during disease manifestations and at the end stage of disease, HSPB8 is highly expressed in the spinal cord of the SOD1-G93A ALS mouse model and in spinal cord specimens of ALS patients (Anagnostou et al, 2010; Crippa et al, 2010). Moreover, HSPB8 was found upregulated in the lateral tract astrocytes of patients with short disease duration (Gorter et al, 2018). In the SOD1-G93A ALS mouse model, the high levels of HSPB8 are confined specifically in anterior horn spinal cord motoneurons that survive at the end stage of disease (Crippa et al, 2010).…”
Section: The Role Of Hspb8 In the Selection Of The Proper Degradativementioning
confidence: 99%
“…The activated microglial and reactive astrocytes also constitute an important element of ALS, which is a lateonset neurodegenerative disease, involving the impaired survival of upper and lower motor neurons (Geser et al, 2008;Yamanaka et al, 2008;Gorter et al, 2019). Neurotoxic glial cells surrounding the motor neurons play a crucial role in ALS.…”
Section: Neurodegenerative Diseasementioning
confidence: 99%